Mythos/Nomos. The Tale and the Law (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2024)
We republish here in her memory an article by Ileana Chirassi Colombo (1936-2023) regarding the relationship between religion and law in classical Greece and other ancient civilizations with an introduction by Alberto Maffi (co-editor of Dike) and Sabina Crippa (professor of History of religions at Ca’ Foscari University of Venice).
Keywords: Mythos; Nomos; Ileana Chirassi Colombo